1996
DOI: 10.1111/j.1469-8137.1996.tb01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mineral nutrition of non‐mycorrhizal and mycorrhizal Norway spruce (Picea abies) seedlings grown in semi‐hydroponic sand culture

Abstract: S U M M A R YIn seedlings of Norway spruce {Picea abies (L.) Karst.), grown in semi-hydroponic sand culture, mycorrhizal infection decreased grow-th (Eltrop & Marschner, 1996). Possible reasotis for this growth depression were investigated in the present study by comparing the plant and fungal biomass distribution and carbon partitioning between non-mycorrhizal and mycorrhizal {Pisolithus tinctorius) plants supplied with ammonium or nitrate as source of N.Despite the high mycorrhizal infection rate (55-71 '\, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…The increased photosynthesis of M plants of group 1 was therefore not reflected in a higher biomass production ( Figure 5). It has been reported that increased photosynthetic rates in mycorrhizal plants with P. tinctorius can be associated with increases (Cairney and Chambers, 1997;Reid et al, 1983) or decreases (Eltrop and Marschner, 1996b) in host biomass. Higher shoot growth has also been observed with no changes in photosynthesis in AM associations (Gavito et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The increased photosynthesis of M plants of group 1 was therefore not reflected in a higher biomass production ( Figure 5). It has been reported that increased photosynthetic rates in mycorrhizal plants with P. tinctorius can be associated with increases (Cairney and Chambers, 1997;Reid et al, 1983) or decreases (Eltrop and Marschner, 1996b) in host biomass. Higher shoot growth has also been observed with no changes in photosynthesis in AM associations (Gavito et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ECM as purely symbiotic to conifer seedlings has been questioned in recent studies (e.g. Conjeaud et al, 1996;Dosskey et al, 1990;Eltorp and Marschner, 1996;Johnson et al, 1997;Zackrisson et al, 1997Zackrisson et al, , 1998, which is corroborated by the observation that the plants with largest biomass had low-to intermediate ECM colonisation levels ( Figure 5). This is probably due to a net C drain from the host, which is most likely to occur if the host is source-limited (e.g.…”
Section: Ectomycorrhizal Colonisation and Plant Growthmentioning
confidence: 75%
“…In any case, the use of results from studies of non-mycorrhizal plants grown on nutrient solutions to explain the performance of conifers in forestry (Kronzucker et al 1996) must be viewed with care. For example, the ammonium uptake by mycorrhizal Norway spruce roots may be associated with particularly high respiration costs (Eltrop and Marschner 1996b). Kreuzwieser et al (1997) suggested that nitrate uptake of non-mycorrhizal roots of young beech seedlings was downregulated drastically in plants with N sufficiency due to an increase of ammonium or amino acid concentrations in the phloem.…”
Section: Figmentioning
confidence: 99%